Noble 3,4-Seco-triterpenoid Glycosides from the Fruits of Acanthopanax sessiliflorus and Their Anti-Neuroinflammatory Effects - Bo-Ram Choi; Hyoung-Geun Kim; Wonmin Ko; Linsha Dong; Dahye Yoon; Seon Min Oh; Young-Seob Lee; Dong-Sung Lee; Nam-In Baek; Dae Young Lee (Antioxidants, 2021)
Acanthopanax sessiliflorus (Araliaceae) have been reported to exhibit many pharmacological activities. Our preliminary study suggested that A. sessiliflorus fruits include many bioactive 3,4-seco-triterpenoids. A. sessiliflorus fruits were extracted in aqueous EtOH and fractionated into EtOAc, n-BuOH, and H2O fractions. Repeated column chromatographies for the organic fractions led to the isolation of 3,4-seco-triterpenoid glycosides, including new compounds. Ultra-high-performance liquid chromatography (UPLC) mass spectrometry (MS) systems were used for quantitation and quantification. BV2 and RAW264.7 cells were induced by LPS, and the levels of pro-inflammatory cytokines and mediators and their underlying mechanisms were measured by ELISA and Western blotting. NMR, IR, and HR-MS analyses revealed the chemical structures of the nine noble 3,4-seco-triterpenoid glycosides, acanthosessilioside G–O, and two known ones. The amounts of the compounds were 0.01–2.806 mg/g, respectively. Acanthosessilioside K, L, and M were the most effective in inhibiting NO, PGE2, TNF-α, IL-1β, and IL-6 production and reducing iNOS and COX-2 expression. In addition, it had inhibitory effects on the LPS-induced p38 and ERK MAPK phosphorylation in both BV2 and RAW264.7 cells. Nine noble 3,4-seco-triterpenoid glycosides were isolated from A. sessiliflorus fruits, and acanthosessilioside K, L, and M showed high anti-inflammatory and anti-neuroinflammatory effects.